Strategic Importance Analysis of PT Telkom Telecommunications Products According to Critical Performance Indicators of The Products in Telecommunication Industry (The Indonesian Journal of Business Administration, 2014)
Abstract - Analysis of product strategic importance needs to be undertaken by companies to manage product portfolio also to develop product. TELKOM needs to assess their product strategic importance, to select which products were more important to the company for forseeable future. This study would help TELKOM in selecting the most important product from six of telecommunication products that has contribute to majority of TELKOM income: Wireline Voice, Astinet, Metro Ethernet, IP Transit, VPN and Speedy, throughexamining critical success factors behindproducts. Critical success factors of products were obtained through studying product development concept using literature review. While, critical success factors of telecommunication industry was obtained through adapted Grounded Theory (GT) method using literature review and knowledgeable employee interview. Based on these findings and knowledgeable employee interview, critical performance indicators of fixed wireline and internet and data products were formed. It was continued by selecting critical performance indicators of TELKOM’s product and determining product strategic importance for 0-3 and 3-5 years ahead using Analytic Hierarchy Process (AHP) model. Resultsfor the most important product for the next 0-3 and 3-5 years were then justified and verified by employee opinions. AHP results indicated that Speedy was the most important product for TELKOM during 0-3 and 3-5 years ahead, with relative weight 0,204 and 0,241 respectively, which strengthen by employee verifications. Therefore, to develop Speedy TELKOM needs to conduct two things, which were maintaining performance of Speedy through its factors and organize different perspectives between Marketing and Product divisions.Keywords: product strategic importance, product’s critical success factors, product portfolio management, telecommunication, product development.